Features of the calculation of the spring element of the regulator of the angle of attack of the cultivator paw - Арендаренко, В. М.; Ларенко, В. В. (Scientific Progress & Innovations, 2017)
On the basis of theoretical studies, an improvement in the construction of the attachment of the working body to cultivator paws is offered. The procedure for calculating the spring element of the regulating and safety device for cultivator paws is presented. The introduction and use of the offered device will increase the uniformity of the stroke of the working organ, and consequently improve the quality of soil cultivation.